Cross-Sectional International Survey to Determine the Educational Interests of Spanish-Speaking Latin American Radiation Oncologists. (2021) - Mailhot Vega, Raymond B.; De La Mata, Dolores; Amendola, Beatriz; Li, Benjamin; Poitevin, Adela; Sarria, Gustavo; Sole, Sebastian; Sher, David J.; Hardenbergh, Patricia
Abstract : PURPOSE: With the existing oncology disparities in Latin America, physician expertise has been cited as a possible contributor to inferior oncologic outcomes in some cancers. As two-dimensional radiotherapy rapidly evolved to intensity-modulated radiation therapy in Latin America, adequate contouring education is an actionable target to improving physician knowledge and clinical outcomes. Yet, topics of interest to Latin American radiation oncologists are underreported. We assessed Latin American interest in a virtual platform for case discussion and identified the educational topics of most interest to them. MATERIALS AND METHODS: A Spanish-language online survey was designed by a team of Latin American educators. The questions assessed professional nationality, desire for an online educational platform for case presentation, career length, and topics of interest. Educational topics included head and neck (H&N), CNS, GI, lung, gynecologic, breast, and pediatric cancers, lymphoma, sarcoma, stereotactic body radiotherapy (SBRT), brachytherapy, and medical physics. RESULTS: One hundred thirty-three surveys were included for analysis. Overall, 127 respondents (98%) affirmed interest in participating in a virtual platform for case discussion and treatment advances. The most popular educational themes were H&N cancers (24%), SBRT (14%), and CNS cancers (13%). Of countries with > 10 respondents, the most popular educational topic remained H&N cancers for Argentina, Chile, and Mexico, but the most popular topic among Peruvian respondents was CNS cancer (27%). CONCLUSION: With international collaboration and a large sample size, we present the first survey results describing Latin American radiation oncology educational interests. Participants were overwhelmingly interested in a virtual platform, and most were specifically interested in H&N cancer education. These results can be used for focused didactic preparation in Latin America. Future efforts should expand on improving representation and outreach among Central American radiation oncologists.